THE INFLUENCE OF CONTENT MARKETING AND ONLINE CUSTOMER REVIEWS ON PURCHASE DECISIONS IN E-COMMERCE - Jhoni Iskandar; Sriwanti Belani; Hadiansyah Ma’sum; Donald Michi Kasetty; Hamdiah (JURNAL ILMIAH EDUNOMIKA, 2026)
The development of the digital landscape has fundamentally changed the way consumers interact with brands and make purchasing decisions on e-commerce platforms. This study aims to analyze the influence of content marketing and online customer reviews on consumer purchasing decisions on e -commerce platforms. Using a quantitative approach, data was collected through a structured online questionnaire distributed to active consumers of e-commerce platforms. The data analysis technique used in this study was Structural Equation Modeling (SEM) or Multiple Linear Regression to test the causal relationship between variables. The results show that both content marketing and online customer reviews have a positive and significant influence on consumer purchasing decisions, both partially and simultaneously. The educational and interactive information components in content marketing have been shown to stimulate initial interest, while the credibility and valence of online customer reviews serve as critical validators that minimize consumer risk perceptions before making a final transaction. The practical implications of this study emphasize the importance for digital business actors to integrate relevant content creation strategies with consumer review reputation management to optimize sales conversions in an increasingly competitive digital market.